Dose Measurements around Spallation Neutron Sources - Fragopoulou, M.; Stoulos, S.; Manolopoulou, M.; Krivopustov, M.; Zamani, M. (HNPS Advances in Nuclear Physics, 2020)
Neutron dose measurements and calculations around spallation sources are of importance for an appropriate shielding study. Two spallation sources, consisted of Pb target, have been irradiated by high-energy proton beams, delivered by the Nuclotron accelerator (JINR), Dubna. Dose measurements of the neutrons produced by the two spallation sources were performed using Solid State Nuclear Track Detectors (SSNTDs). In addition, the neutron dose after polyethylene and concrete was calculated using phenomenological model based on empirical relations applied in high energy Physics. Analytical and experimental neutron benchmark analysis has been performed using the transmission factor. A comparison of experimental results with calculations is given.